A CLINICAL STUDY TO EVALUATE THE EFFICACY OF GUNJA SEEDS AS A LOCAL APPLICATION IN THE MANAGEMENT OF INDRALUPTA - Sachin, Patil; Sagar, Narode; Kavita, Patil (International Journal of Ayurveda and Pharma Research, 2016)
'Indralupta or 'Alopecia areata' is mainly a cosmetic condition where we find a patchy loss of previously existing body hairs. When we go through different Ayurvedic texts lot of references are found indicating the use of poisonous drugs as an external application for various types of diseases & alopecia areata is a disease which requires a topical type of treatment. It is one of the common therapeutic problems which challenge the skill of the people working in the field of dermatology.Ayurveda accepts the utility of toxic substances in treating the diseases keeping in mind some medicinal properties hidden inside. A thorough literature research gave us the scope to expect some good results from a herbal irritant drug - 'Gunja'.The present study was carried out on 20 patients diagnosed with Indralupta. Lepa of fine powder of the seeds of Gunja was used for topical application two times per day for 56 days.The study shown that in 40% of cases complete reoccurrence of hair growth was noted where as 50% showed partial growth and 10% showed no change at all. According to the modern science the need of activation of the hair follicles through induction of mild irritant contact dermatitis is necessary in this disease for regeneration and growth of hair with its inherent properties, Gunjabeejalepa irritates the lesions with Tikshnaguna and Ushna Veerya and Tikta rasa. Combine these virtues act to irritate and activate the hair follicles thereby promoting hair growth of the affected part.